Nitrogen-doped defect carbon sphere material loaded with monatomic Ni and application of nitrogen-doped defect carbon sphere material in lithium-sulfur battery

Through nitrogen-doped defective carbon ball material loaded with single atom Ni, the problem of polysulfide shuttle effect and slow reaction kinetics in lithium-sulfur batteries is solved, the specific capacity and cycle stability of the battery are improved, and the efficient lithium-sulfur is achieved Battery performance is improved.

CN119297530APending Publication Date: 2025-01-10INST OF NEW MATERIALS & IND TECH WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411279459.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Lithium sulfur batteries have limited their commercial applications due to the insulating properties of sulfur and Li2S/Li2S, which lead to low utilization of active substances, poor structural collapse, poor circulation performance, polysulfide shuttle effect and slow reaction kinetics.

Method used

Using nitrogen-doped defective carbon sphere materials that are loaded with single atom Ni can exist stably through strong interaction between Ni atoms and N atoms, design the interface vacancy defects, form an electron transfer network structure, combine the catalytic activity of single atom Ni to improve polysulfide The redox reaction efficiency and physical adsorption capacity of substances.

Benefits of technology

The specific capacity, rate performance and cycle stability of lithium sulfur batteries have been significantly improved. The discharge capacity of the first circle reaches 1157mAh/g, the capacity remains at 81.5% at 2C ratio, and the attenuation rate after 150 cycles is as low as 0.01%, and the low cost is achieved. , efficient preparation and commercial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297530A_ABST
    Figure CN119297530A_ABST
Patent Text Reader

Abstract

The invention provides a nitrogen-doped defect carbon sphere material loaded with monatomic Ni and application of the nitrogen-doped defect carbon sphere material in a lithium-sulfur battery. The problems of Li negative electrode corrosion, irreversible capacity fading and the like caused by deposition of insulating sulfur and polysulfide on the surface of a pole piece, volume expansion of a material in the charging and discharging process, a shuttle effect and slow reaction kinetics in the lithium-sulfur battery are solved. According to the catalyst, by designing monatomic Ni with maximum catalytic efficiency, highly dispersed monatomic Ni with a stable structure and strong interaction and multiple effects of constructing carbon sphere interface vacancy defects, physical limitation, chemical adsorption and catalytic action on polysulfide are synergistically realized, and the reaction kinetics and mass transfer rate of the catalyst are improved. When the catalyst is applied to the lithium-sulfur battery as a diaphragm modification material, the specific capacity, the rate capability and the cycle performance of the lithium-sulfur battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-sulfur batteries, and in particular to a nitrogen-doped defective carbon sphere material loaded with single-atom Ni and an application thereof in lithium-sulfur batteries. Background Art

[0002] Lithium-sulfur batteries are considered to be an ideal alternative to lithium-ion batteries due to their excellent energy density (2600Wh / kg). However, there are still many problems that limit the commercial application of lithium-sulfur batteries: 1) Due to the insulating properties of sulfur and Li2S / Li2S2, the utilization rate of active materials is low, and Li2S is deposited on the surface of the electrode to form a passivation layer, resulting in a decrease in the discharge specific capacity of the lithium-sulfur battery; 2) The volume expansion of sulfur during the cycle will cause the structural collapse of the positive electrode material, resulting in poor cycle performance of the lithium-sulfur battery; 3) Defects such as the "shuttle effect" of soluble polysulfides and slow reaction kinetics will cause adverse conditions such as loss of active materials, low coulombic efficiency, capacity decay and battery self-discharge.

[0003] In order to solve the above problems, improving the utilization of sulfur on effective host materials is a feasible strategy to improve the performance of lithium-sulfur batteries. In this regard, carbon materials have attracted much attention due to their good conductivity, porous structure and large specific surface area. Carbon materials prevent the shuttling of polysulfides through physical constraints, but they cannot completely solve the problem of polysulfide dissolution in electrolytes. At the same time, the slow conversion reaction kinetics from polysulfides to Li2S / Li2S2 remains a key issue hindering the development of lithium-sulfur batteries. In addition, non-polar carbon materials have poor adsorption of polar polysulfides, which is not enough to completely suppress the "shuttle effect" of polysulfides, resulting in serious capacity decay of lithium-sulfur batteries under long cycles. Therefore, it is necessary to introduce efficient catalytic active sites to further accelerate the conversion of polysulfides.

[0004] Single-atom catalysts have good application prospects in lithium-sulfur batteries because their single metal center can achieve maximum atomic utilization and high catalytic activity. Reasonable design of the configuration relationship of active sites in the catalyst material interface is conducive to the redistribution of charge, thereby affecting the reaction energy barrier, having a positive effect on the reaction kinetics of polysulfide conversion, and ultimately improving the electrochemical performance of lithium-sulfur batteries on a macro scale. However, metal single atoms tend to agglomerate during the charge and discharge process, which will seriously lead to a decrease in the electrochemical performance of the battery, and the current material synthesis for constructing atomic structures requires cumbersome preparation processes. Therefore, it is a huge challenge to develop a novel and simple strategy to obtain stable and efficient metal single-atom catalysts. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a nitrogen-doped defective carbon sphere material loaded with single-atom Ni and its application in lithium-sulfur batteries.

[0006] The technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a nitrogen-doped defective carbon sphere material loaded with single-atom Ni, which is a nitrogen-doped defective carbon sphere with interface vacancy defects formed by the escape of Cd atoms, and the surface of the nitrogen-doped defective carbon sphere is in-situ loaded with single-atom Ni.

[0008] Preferably, the preparation method comprises the following steps:

[0009] S1: dissolving nickel salt, cadmium salt and ethylenediamine in a solvent to obtain a mixed solution;

[0010] S2: adding tetraethyl silicate to the above mixed solution to react to obtain a spherical SiO2 skeleton, then adding resorcinol and formaldehyde to react in a protective gas, and after the reaction is completed, centrifugation and washing to obtain a precursor;

[0011] S3: The precursor is calcined at high temperature, and after cooling, it is immersed in a NaOH solution to remove the spherical SiO2 skeleton, and after centrifugal washing and drying, a nitrogen-doped defective carbon sphere catalyst loaded with single-atom Ni is obtained.

[0012] Preferably, in step S1, the anions of the nickel salt and the cadmium salt are NO3 - 、SO4 2- , Cl - 、C2O4 2- Any one or more of the mixture.

[0013] Preferably, in step S1, the molar ratio of the total amount of nickel salt and cadmium salt to ethylenediamine is 0.68-0.98:100, wherein the molar ratio of nickel salt to cadmium salt is 1.2-2.9:1.

[0014] Preferably, in steps S1 and S2, the volume of ethylenediamine is 0.2-1.5% of the volume of the solvent, and the volume of tetraethyl silicate is 5-8% of the volume of the mixed solution.

[0015] Preferably, in step S2, the ratio of resorcinol to formaldehyde is 0.2-3.5 g / ml.

[0016] Preferably, in step S2, the protective gas is N2 and the reaction time is 18-30 hours.

[0017] Preferably, in step S3, the high temperature calcination temperature is 700-900°C and is kept for 2-6 hours.

[0018] The second aspect of the present invention is to provide the use of the nitrogen-doped defective carbon sphere material loaded with single-atom Ni as described above in a lithium-sulfur battery, wherein the nitrogen-doped defective carbon sphere material loaded with single-atom Ni is coated on the surface of a diaphragm for modification.

[0019] Preferably, the nitrogen-doped defective carbon sphere material loaded with single-atom Ni is mixed with a binder at a mass ratio of 3.5-4.5:1, NMP is added for sufficient grinding to obtain a catalyst slurry, the catalyst slurry is scraped onto the diaphragm, and the modified diaphragm is obtained after drying.

[0020] The beneficial effects of the present invention are as follows:

[0021] 1. In the nitrogen-doped defective carbon sphere catalyst loaded with single-atom Ni prepared by the present invention, Ni is designed to be uniformly dispersed at the carbon sphere interface in a single-atom state, and is stable and not easy to agglomerate by relying on the strong interaction between Ni atoms and N atoms. Since the single-atom Ni active site has a maximized atomic utilization, it can significantly improve the efficiency of chemical capture of polysulfides and accelerate the redox reaction activity of polysulfides. In addition, the strong interaction between single Ni atoms is also conducive to charge redistribution, reducing the activation energy barrier, thereby further accelerating Liquid-solid bidirectional transformation kinetics.

[0022] 2. The present invention innovatively synthesizes a nitrogen-doped carbon sphere with vacancy defects, and the carbon spheres are interconnected to form a network structure for electron transfer as a whole. Compared with most of the reported carbon materials, the catalyst of the present invention not only maintains the advantages of high conductivity, structural stability, large specific surface area, etc. that are widely possessed by carbon materials, but also utilizes the interface vacancy defects designed by Cd escape. As electrons transfer to N atoms, the vacancies that lose electrons enhance the physical adsorption and catalytic activity of polysulfides, thereby limiting the "shuttle effect" of polysulfides to protect the lithium negative electrode. In addition, the vacancy defects at the interface provide abundant channels for mass transfer in lithium-sulfur batteries, which further facilitates the rapid transmission of ions and electrons.

[0023] 3. By coupling the efficient chemical capture and catalytic activity of single-atom Ni with the physical adsorption and rapid mass transfer channels enhanced by interfacial vacancy defects, and combining the high conductivity, large number of reactive sites and strong structural skeleton of the catalyst, the components synergistically enhance the specific capacity, rate performance and cycle stability of the lithium-sulfur battery. The first-cycle discharge capacity of the lithium-sulfur battery at a rate of 0.1C can reach 1157mAh / g, and even at a rate of 2C, it has a specific capacity of 880mAh / g; in a 150-cycle cycle test at a rate of 1C, its capacity retention rate reached 81.5%, and after 300 cycles, its per-cycle attenuation rate was as low as 0.01%.

[0024] 4. The raw materials for the preparation of this catalyst are low-priced, the synthesis method is simple, the equipment is highly operable and has excellent electrochemical performance. Currently, it can be scaled up to kilograms, so it has high economic benefits and commercial application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0026] Figure 1 This is the SEM of the nitrogen-doped defective carbon sphere catalyst loaded with single-atom Ni in Example 1;

[0027] Figure 2 (a) TEM, (b) STEM, and (cf) Mapping of the nitrogen-doped defective carbon sphere catalyst loaded with single-atom Ni in Example 1;

[0028] Figure 3 XPS of the nitrogen-doped defective carbon sphere catalyst loaded with single-atom Ni in Example 1: (a) C1s spectrum, (b) N1s spectrum and (c) Ni 2p spectrum;

[0029] Figure 4 (a) nitrogen adsorption-desorption curves and (b) pore size distribution diagrams of the catalysts of Example 1 and Comparative Examples 1-3;

[0030] Figure 5 The first cycle charge and discharge curves of the catalysts of Example 1 and Comparative Examples 1-3 applied to lithium-sulfur batteries;

[0031] Figure 6 The rate performance diagram of the catalysts of Example 1 and Comparative Examples 1-3 applied in lithium-sulfur batteries;

[0032] Figure 7 The cycle performance diagram of the catalysts of Example 1 and Comparative Examples 1-3 applied in lithium-sulfur batteries;

[0033] Figure 8 CV curves of the catalysts of Example 1 and Comparative Examples 1-3 applied in lithium-sulfur batteries;

[0034] Fig. 9 The reaction kinetics data diagrams of the catalysts of Example 1 and Comparative Examples 1-3 applied in lithium-sulfur batteries: (a) constant potential charging test, (b) Li2S conversion rate comparison diagram and (cf) Li2S deposition diagram. DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0036] Example 1

[0037] First, 60 mL of deionized water, 50 mL of ethanol and 0.5% of the solvent volume of ethylenediamine were mixed evenly, and then nickel nitrate and cadmium nitrate (Ni 2+ : Cd 2+ : The molar ratio of ethylenediamine is 0.5:0.26:100), and stirring is continued until it is completely dissolved; then 6mL of tetraethyl silicate is added to the above mixed solution, and when the solution turns white, 0.7g of resorcinol and 1.2mL of formaldehyde are added, and the reaction is maintained for 24 hours under nitrogen protection. After the reaction is completed, the mixed solution is centrifuged, and the precursor is separated and washed with deionized water until the solution is neutral; then the precursor is transferred to a tubular furnace and calcined at high temperature in a nitrogen atmosphere, and the program is set to 800℃ for 3h. After cooling to room temperature, it is transferred to a 4mol / L NaOH solution for immersion, and is placed at 50℃ for immersion for 24h to remove the SiO2 core in the precursor, followed by centrifugation and washing with deionized water until the solution is neutral, and finally nitrogen-doped defective carbon spheres (Ni@NVC-1) loaded with single-atom Ni are obtained.

[0038] The morphology of the prepared catalyst is Figure 1-Figure 2 As shown in the SEM, TEM, STEM and Mapping, the catalyst is composed of multiple carbon spheres with uniform particle size and smooth surface connected to each other, and the single-atom Ni is distributed in the carbon spheres in a single-atom state without obvious clusters. Combining the results of Mapping and ICP, it can be seen that the N content in the catalyst is 8.11wt%, the Ni content is 0.261wt%, and the Cd content is 0, and the elements are evenly distributed in the carbon spheres. Figure 3 The XPS test analyzed the element valence state and atomic coordination of Example 1. The peaks at 284.8 eV, 286.2 eV and 289.4 eV in the C1s spectrum correspond to CC, CN and O=CO, respectively. The peaks at 398.5 eV, 400.5 eV, 401.3 eV and 404.0 eV in the N1s spectrum correspond to pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and oxidized nitrogen, respectively. The peaks at 856.3 eV and 873.5 eV in the Ni 2p spectrum correspond to Ni 2+ , XPS analysis results confirmed that Ni was mainly in ionic state and existed in the form of Ni-N.

[0039] Example 2

[0040] First, 60 mL of deionized water, 50 mL of ethanol and 0.8% of the solvent volume of ethylenediamine were mixed evenly, and then nickel chloride and cadmium chloride (Ni 2+ : Cd 2+ : The molar ratio of ethylenediamine is 0.55:0.28:100), and stirring is continued until it is completely dissolved; then 7mL of tetraethyl silicate is added to the above mixed solution, and when the solution turns white, 0.8g of resorcinol and 1.4mL of formaldehyde are added, and the reaction is maintained for 24 hours under nitrogen protection. After the reaction is completed, the mixed solution is centrifuged, and the precursor is separated and washed with deionized water until the solution is neutral; then the precursor is transferred to a tubular furnace and calcined at high temperature in a nitrogen atmosphere, and the program is set to 800℃ for 5h. After cooling to room temperature, it is transferred to a 4mol / LNaOH solution for immersion, and is placed at 50℃ for immersion for 24h to remove the SiO2 core in the precursor, followed by centrifugation and washing with deionized water until the solution is neutral, and finally nitrogen-doped defective carbon spheres (Ni@NVC-2) loaded with single-atom Ni are obtained.

[0041] Example 3

[0042] First, 60 mL of deionized water, 50 mL of ethanol and 1.0% of the solvent volume of ethylenediamine were mixed evenly, and then nickel sulfate and cadmium sulfate (Ni 2+ : Cd 2+ : The molar ratio of ethylenediamine is 0.6:0.3:100), and stirring is continued until it is completely dissolved; then 8mL of tetraethyl silicate is added to the above mixed solution, and when the solution turns white, 1.1g of resorcinol and 2.1mL of formaldehyde are added, and the reaction is maintained for 24 hours under nitrogen protection. After the reaction is completed, the mixed solution is centrifuged, and the precursor is separated and washed with deionized water until the solution is neutral; then the precursor is transferred to a tubular furnace and calcined at high temperature in a nitrogen atmosphere, and the program is set to 800℃ for 4h. After cooling to room temperature, it is transferred to a 4mol / L NaOH solution for immersion, and is placed at 50℃ for immersion for 24h to remove the SiO2 core in the precursor, followed by centrifugation and washing with deionized water until the solution is neutral, and finally nitrogen-doped defective carbon spheres (Ni@NVC-3) loaded with single-atom Ni are obtained.

[0043] Comparative Example 1

[0044] Compared with Example 1, the catalyst of Comparative Example 1 does not contain vacancy defects in the carbon sphere structure. Except that cadmium nitrate is not added in step S1 of Example 1, the remaining steps are consistent with Example 1, and the obtained catalyst is nitrogen-doped carbon sphere (Ni@NC) loaded with single-atom Ni.

[0045] Comparative Example 2

[0046] Compared with Example 1, the catalyst of Comparative Example 2 does not contain single-atom Ni. Except that nickel nitrate is not added in step S1 of Example 1, the remaining steps are consistent with Example 1, and the obtained catalyst is nitrogen-doped defective carbon spheres (NVC).

[0047] Comparative Example 3

[0048] Compared with Example 1, the catalyst of Comparative Example 3 contains neither single-atom Ni nor vacancy defects. Except that nickel nitrate and cadmium nitrate are not added in step S1 of Example 1, the remaining steps are consistent with Example 1, and the obtained catalyst is nitrogen-doped carbon spheres (NC).

[0049] Comparative Example 4

[0050] Compared with Example 1, the catalyst of Comparative Example 4 has the following features except that Ni 2+ : Cd 2+ The molar ratio of ethylenediamine is 0.25:0.15:100, and the remaining steps are consistent with those in Example 1. The obtained catalyst is Ni@NVC-4.

[0051] Comparative Example 5

[0052] Compared with Example 1, the catalyst of Comparative Example 5 has the following features except that Ni 2+ : Cd 2+ The molar ratio of ethylenediamine is 0.73:0.38:100, and the remaining steps are consistent with those in Example 1. The obtained catalyst is Ni@NVC-5.

[0053] Comparative Example 6

[0054] Compared with Example 1, the catalyst of Comparative Example 6 is the same as Example 1 except that in step S2 of Example 1, the addition amount of tetraethyl silicate is 9 mL, the addition amount of resorcinol is 0.3 g, and the addition amount of formaldehyde is 0.5 mL. The remaining steps are consistent with Example 1, and the obtained catalyst is Ni@NVC-6.

[0055] Comparative Example 7

[0056] Compared with Example 1, the catalyst of Comparative Example 7 is the same as Example 1 except that in step S2 of Example 1, the addition amount of tetraethyl silicate is 10 mL, the addition amount of resorcinol is 3.6 g, and the addition amount of formaldehyde is 4.8 mL. The remaining steps are consistent with Example 1, and the obtained catalyst is Ni@NVC-7.

[0057] Comparative Example 8

[0058] Compared with Example 1, the catalyst of Comparative Example 8 is consistent with Example 1 except that the high-temperature calcination procedure in step S3 of Example 1 is set to 600° C. for 7 h. The remaining steps are consistent with Example 1, and the obtained catalyst is Ni@NVC-8.

[0059] Comparative Example 9

[0060] Compared with Example 1, the catalyst of Comparative Example 9 is the same as Example 1 except that the high temperature calcination procedure in step S3 of Example 1 is set to 1000° C. for 1 h. The remaining steps are the same as those of Example 1, and the obtained catalyst is Ni@NVC-9.

[0061] The catalysts prepared in the above Examples 1-3 and Comparative Examples 1-9 were tested by combining ICP, Mapping and XPS to obtain the contents of N, Ni and Cd. The results are listed in Table 1.

[0062] Table 1 Element content results of catalysts in Examples 1-3 and Comparative Examples 1-9

[0063]

[0064]

[0065] The catalysts prepared in Examples 1-3 and Comparative Examples 1-9 were used to modify the diaphragm of a lithium-sulfur battery. The performance of the lithium-sulfur battery is listed in Table 2.

[0066] Table 2 Lithium-sulfur battery performance of catalysts in Examples 1-3 and Comparative Examples 1-9

[0067]

[0068] As shown in the results of Table 1-2, Examples 1-3 provided by the present invention all have good specific capacity, rate performance and cycle performance, and the Cd atoms in Examples 1-3 all escape during the high-temperature calcination stage to form vacancy defects. The Ni@NC catalyst of Comparative Example 1 contains only single-atom Ni but no vacancy defects, the NVC catalyst of Comparative Example 2 contains only vacancy defects but no single-atom Ni, the NC catalyst of Comparative Example 3 does not contain both single-atom Ni and vacancy defects, and Comparative Examples 4-9 are synthesis conditions that are not within the preferred range of the patent, so the electrochemical performance of their lithium-sulfur batteries is reduced to varying degrees, indicating that the method of regulating single-atom Ni and vacancy provided by the present invention synergistically improves the battery performance of the catalyst in lithium-sulfur batteries, showing good application prospects in real life.

[0069] To further explain the superiority of Example 1 in physical adsorption and chemical adsorption, BET tests were performed on Example 1 and Comparative Examples 1-3. The results are as follows: Figure 4As shown, the nitrogen adsorption - desorption curves of the catalysts in Example 1 and Comparative Examples 1 - 3 are type I curves, belonging to the microporous type, and the pore size distribution is concentrated in the range of 2 - 5 nm. Among them, the specific surface areas of the catalysts in Example 1 and Comparative Examples 1 - 3 are 1474.8 m 2 / g, 1444.1 m 2 / g, 1246.3 m 2 / g, and 709.5 m 2 / g respectively. Example 1 has the largest specific surface area and a large number of microporous structures, which is conducive to the superposition effect of micropores and vacancy defects on free molecular groups in the electrolyte. Therefore, it has unique adsorption selectivity and extremely strong adsorption capacity, which is beneficial to obtaining higher capacity, better cycle stability, and longer service life.

[0070] The catalysts of Example 1 and Comparative Examples 1 - 3 were applied to lithium - sulfur batteries, and the electrochemical performance as shown in Figure 5-Figure 9 was obtained and the reaction kinetics in the lithium - sulfur battery was further analyzed to elaborate the mechanism of the excellent battery performance of Example 1. As shown in the first - cycle charge - discharge curve in Figure 5 , the catalyst of Example 1 has the largest specific capacity, which can reach 1157 mAh / g at 0.1 C; in the rate performance graph shown in Figure 6 , the catalyst of Example 1 still has a specific capacity of 880 mAh / g at 2 C, and can return well to the small - current density after the high - current density test, showing excellent rate performance; in the cycle performance graph shown in Figure 7 , the catalyst of Example 1 also maintains the best capacity retention rate, which can reach 81.5% after 150 cycles. When cycling to 300 cycles, its per - cycle decay rate is as low as 0.01%, showing good cycle stability. In the CV curve graph shown in Figure 8 , the catalyst of Example 1 shows two oxidation peaks at 2.31 V and 2.38 V during the charging process. The oxidation peak with a lower potential is related to the formation of Li2S n (n > 2), while the peak with a higher potential is related to the formation of S8; during the discharging process, two reduction peaks appear in the CV curve, and the peak values are approximately 2.29 V and 2.03 V respectively, corresponding to the reduction of solid S8 to soluble Li2S x (4 < x < 8) and the reduction of Li2S x to insoluble Li2S / Li2S2. Compared with the CV curves of the catalysts in Comparative Examples 1 - 3, the redox peaks of the catalyst in Example 1 are sharper, the corresponding reduction peak shows a positive shift, and the oxidation peak shows a negative shift, indicating that the conversion of LiPSs is more complete and the polarization degree is reduced. The potential shifts of all four peaks also prove that the catalyst of Example 1 can promote the conversion between liquid Li2S x and liquid LiPSs.

[0071] In addition, the kinetics of LiPSs conversion was investigated by constant potential charging tests at slightly higher overpotentials to promote the complete conversion of insoluble Li2S into soluble LiPSs. Fig. 9 In (a), compared with the catalysts of Comparative Examples 1-3, the Li2S conversion rate on the surface of the catalyst of Example 1 is faster and the oxidation current is larger, which indicates that the oxidation overpotential is lower during the conversion of LiPSs; Fig. 9 Among the catalysts shown in (b), Example 1 has a maximum conversion rate of Li2S of 14.7%; because the catalyst of Example 1 has efficient single-atom catalytic active sites and interface vacancy defects, the dual effects can promote the nucleation and growth of Li2S, thereby depositing more Li2S in the constant potential discharge curve, as shown in FIG. Fig. 9 (cf) shows that the catalyst of Example 1 can deposit 244.40 mAh / g of Li2S and has the fastest reaction kinetics.

[0072] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the protection scope of the technical solution of the present invention.

[0073] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A nitrogen-doped defective carbon sphere material loaded with single-atom Ni, characterized in that: The carbon sphere is a nitrogen-doped defective carbon sphere having an interface vacancy defect formed by the escape of Cd atoms, and a single atom Ni is in-situ loaded on the surface of the nitrogen-doped defective carbon sphere.

2. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 1, characterized in that: The preparation method comprises the following steps: S1: dissolving nickel salt, cadmium salt and ethylenediamine in a solvent to obtain a mixed solution; S2: adding tetraethyl silicate to the above mixed solution to react to obtain a spherical SiO2 skeleton, then adding resorcinol and formaldehyde to react in a protective gas, and after the reaction is completed, centrifugation and washing to obtain a precursor; S3: The precursor is calcined at high temperature, and after cooling, it is immersed in a NaOH solution to remove the spherical SiO2 skeleton, and after centrifugal washing and drying, a nitrogen-doped defective carbon sphere catalyst loaded with single-atom Ni is obtained.

3. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 2, characterized in that: In step S1, the anions of the nickel salt and the cadmium salt are NO3 - 、SO4 2- , Cl - 、C2O4 2- Any one or more of the mixture.

4. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 2, characterized in that: In step S1, the molar ratio of the total amount of nickel salt and cadmium salt to ethylenediamine is 0.68-0.98:100, wherein the molar ratio of nickel salt to cadmium salt is 1.2-2.9:

1.

5. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 2, characterized in that: In steps S1 and S2, the volume of ethylenediamine is 0.2-1.5% of the volume of the solvent, and the volume of tetraethyl silicate is 5-8% of the volume of the mixed solution.

6. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 2, characterized in that: In step S2, the ratio of resorcinol to formaldehyde is 0.2-3.5 g / ml.

7. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 2, characterized in that: In step S2, the protective gas is N2 and the reaction time is 18-30h.

8. The nitrogen-doped defective carbon sphere material loaded with single-atom Ni according to claim 2, characterized in that: In step S3, the high temperature calcination temperature is 700-900°C and is kept for 2-6 hours.

9. Application of the nitrogen-doped defective carbon sphere material loaded with single-atom Ni as claimed in any one of claims 1 to 8 in a lithium-sulfur battery, characterized in that: The nitrogen-doped defective carbon sphere material loaded with single-atom Ni is coated on the surface of the diaphragm for modification.

10. The use according to claim 9, characterized in that: The nitrogen-doped defective carbon sphere material loaded with single-atom Ni is mixed with a binder at a mass ratio of 3.5-4.5:1, NMP is added for sufficient grinding to obtain a catalyst slurry, the catalyst slurry is scraped on the diaphragm, and the modified diaphragm is obtained after drying.